2019
DOI: 10.35631/ijepc.432008
|View full text |Cite
|
Sign up to set email alerts
|

Using Origami to Enhance Visual and Mathematical Thinking Skills Among the Autistics

Abstract: Autism is a general term for a group of complex disorders that affects brain development (Autism Society of America, (2014). “Autos” means ‘you in your own self’ which is described as ‘a runaway from reality’ (Leo Kanner, (1943). Autism has its own specializations which are mathematical (Baron Cohen et al 2001), and visual thinkers (Karren Piece, 2010). They can follow steps and create designs in more creative ways than others. This paper will deliberate on how the origami technique helps escalate the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…After all research converges that the mathematics course is made more interesting by using manipulative materials (Mere et al, 2019). Moreover, Hermes solved all the original problems correctly, a fact that converges with the literature (Bakar & Fauzi, 2019;Fauziyah et al, 2021;Peltier et al, 2019). Furthermore, Hermes identified alone the illusion of linearity when solving original problems using simultaneous manipulative material (cf.…”
Section: Further Discussion and Suggestionssupporting
confidence: 79%
See 1 more Smart Citation
“…After all research converges that the mathematics course is made more interesting by using manipulative materials (Mere et al, 2019). Moreover, Hermes solved all the original problems correctly, a fact that converges with the literature (Bakar & Fauzi, 2019;Fauziyah et al, 2021;Peltier et al, 2019). Furthermore, Hermes identified alone the illusion of linearity when solving original problems using simultaneous manipulative material (cf.…”
Section: Further Discussion and Suggestionssupporting
confidence: 79%
“…Results showed that these children developed strategies for solving mathematical problems when appropriate educational manipulatives were used. Also, Bakar and Fauzi (2019) found that children on autism spectrum work on mathematics problems more easily when instruction is on use of manipulatives materials. More specifically, the researchers used origami, the Japanese art of paper folding, during teaching of mathematics and learning outcomes for children with autism (and children with Asperger syndrome) were positive.…”
Section: Theoretical Considerations About Use Of Manipulative Materialsmentioning
confidence: 99%